Age of the donor affects the nature of in vitro cultured human dental pulp stem cells - Heba Alzer (Elsevier, 2021)
Objectives: The dental pulp stem cells (DPSCs) of six donors (three young donors aged < 19 years and three adult donors aged > 25 and < 30 years) were characterized for their stem cell marker expression and differentiation potential to study the effect of donor age on DPSCs in vitro. Methods: DPSCs were cultured in αMEM supplemented with 20% fetal calf serum (conventional conditions) or on fibronectin-coated flasks with neurobasal medium supplemented with B27, bFGF and EGF (alternative conditions). DPSCs were characterized by immunofluorescence staining to detect the neural crest/mesenchymal stem cells markers P75 and CD146, respectively. The differentiation potential was tested by the induction of DPSCs into osteogenic, adipogenic and glial lineages and then by detecting the corresponding markers osteocalcin, lipidtox and S100ß, respectively. Results: The DPSCs of the young donors expressed CD146 only under the conventional conditions and expressed P75 regardless of the culture conditions. However, the DPSCs of adult donors expressed CD146 only under the alternative conditions and expressed P75 only under conventional conditions. Only the DPSCs of the young donors differentiated into the glial linage. The DPSCs of the adult donors differentiated more efficiently into the adipogenic linage. Osteogenic differentiation was comparable. Conclusion: Donor age affects the expression of stem cell markers and differentiation potential of DPSCs. Moreover, the effect of culture conditions on DPSCs is age dependent.